Técnicas motivadoras y su incidencia en el proceso enseñanza aprendizaje del idioma inglés en los estudiantes del 8vo año de la unidad educativa Eugenio Espejo Babahoyo provincia de los Ríos durante el periodo 2017-2018 - Cercado Miranda, Silvia Lisseth (2017)
The present research project, whose theme is motivating techniques and its incidence in the process of teaching English language learning, has the purpose of knowing the varieties of motivating techniques, to apply them to the different types of students of the educational unit Eugenio Mirror, favoring students. To obtain an academic achievement, and to deepen the content of knowledge and at the same time to develop interest, the ability to set goals throughout their life, with a calm, pleasant atmosphere to express their concerns favoring, their logical mentality, interactive in the English language. It consists of four chapters in which the approach of the selected problem is developed the general and specific objectives that are applied to the research and the reasons that justify for a certain solution, also constitutes the theoretical framework of the investigation, antecedents, theoretical posture and the signaling of variables. Surveys will be conducted to obtain complete information for parents, teachers and students to detail all the information in tabulations and surveys to give recommendations, general and specific conclusions of the research to complement the solution to the problem by determining the Positive and at the same time fundamental results.